Putting the "Alternative" Back into ADR - Andrew B. Mamo (Washington University Journal of Law and Policy, 2023)
Alternative Dispute Resolution (ADR) plays a dominant role in the resolution of most legal disputes whether by choice, contractual duty, or mandate of court. This Article argues that because of its growth and prominence, alternative dispute resolution is no longer “alternative.” The Author claims that ADR’s status as a default process in modern litigation contradicts its foundational principles of voluntariness and the strengthening of legal rights. The appeal of ADR for lawyers and judges is efficiency: saving time and controlling litigation costs. The Author argues there are more ways to promote those goals without defaulting to ADR. The Article advocates for restoring ADR’s “alternative” status in order to preserve access to the law and to empower litigants to engage with conflict on their own terms.
Keywords: ADR; Alternative dispute resolution; alternative; voluntary; mandatory; efficiency; costs; access; courts; litigants; conflict; contracts; mandate; resolution; lawyers; judges; legal rights; default; process